In Sharing We Trust. Taking Advantage of a Diverse Consortium to Build a Transparent Data Service in Catalonia - Clara Llebot; Mireia Alcalá; Lluís M. Anglada i de Ferrer (International Journal of Digital Curation)
The Consorci de Serveis Universitaris de Catalunya (CSUC) is a consortium that serves 13 universities and 33 research centers in Catalonia and neighboring communities. In 2017 the Consortium created an Open Science department to collaborate with universities and research centers on facilitating the adoption of Open Science requirements. Even though CSUC also offers services to researchers directly (for example, its supercomputing resources), this report will focus on CSUC’s work with its member institutions to create and offer data management services. We will explain how CSUC has led the creation of a robust shared governance system, and how it takes advantage of the diversity of its members to create useful, high quality, and transparent services for all researchers in the Catalan research system. Through sharing each other’s experiences, values and priorities, the result is better than separate ad-hoc solutions. The process also creates a community of practitioners that develop expertise together with the help of professional development opportunities organized by CSUC, like recurrent self-learning labs focused on data curation tools, techniques and processes.